Gomphonema grande sp. nov., a new diatom (Bacillariophyta) from the Democratic Republic of the Congo, Tropical Africa - Karthick, Balasubramanian; Kociolek, Patrick John; Taylor, Jonathan C; Cocquyt, Christine (Phytotaxa, 2016)
Gomphonema grande sp. nov. is described from a single sample collected from the Congo River Basin, Tropical Africa. The morphological features of the new species are described and documented through light microscopy and scanning electron microscopy analyses. Gomphonema grande differs from most species of the genus by its relatively large size, robust valves, unique shape, and distinctive suite of valve features such as a labium-shaped internal stigma opening. Further discussion on the diverse nature of certain characters in the genus Gomphonema is presented.